Implementasi Transformasi Digital pada Penjualan Perlengkapan Bayi melalui Rancang Bangun Sistem Informasi dengan Metode Rapid Application Development - Hidayatullah Ruslan; Eliyah Acantha Manapa Sampetoding; Yulita Sirinti Pongtambing (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
In the era of digital transformation, the utilization of information technology in business activities has become an important factor in improving operational efficiency and effectiveness. Dzikri Baby Shop, a business engaged in the sale of baby equipment, still faces challenges in managing sales transactions and inventory manually, which may lead to recording errors, process delays, and less optimal customer service. This study aims to design and develop a sales information system for Dzikri Baby Shop to support digital transformation in its business processes. The system development method used in this research is Rapid Application Development (RAD), as it enables software to be developed in a relatively short time through an iterative approach and active user involvement. The system developed includes product data management, sales transaction processing, inventory control, and report generation. The testing results using the Black Box Testing method show that all system features function in accordance with user requirements. Therefore, the implementation of this sales information system is expected to improve operational efficiency, accelerate transaction processes, minimize errors in data management, and enhance the quality of customer service.